2004
DOI: 10.1128/jvi.78.15.8036-8046.2004
|View full text |Cite
|
Sign up to set email alerts
|

Degenerate In Vitro Genetic Selection Reveals Mutations That Diminish Alfalfa Mosaic Virus RNA Replication without Affecting Coat Protein Binding

Abstract: The alfalfa mosaic virus (AMV) RNAs are infectious only in the presence of the viral coat protein; however, the mechanisms describing coat protein's role during replication are disputed. We reasoned that mechanistic details might be revealed by identifying RNA mutations in the 3-terminal coat protein binding domain that increased or decreased RNA replication without affecting coat protein binding. Degenerate (doped) in vitro genetic selection, based on a pool of randomized 39-mers, was used to select 30 varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…The A4, G3, C3, and GC3 mutations can be added to a collection of 3Ј nucleotide substitutions that disrupt replication. In general, AMV RNA replication is sensitive to nucleotide substitutions in the 3Ј UTR, and a number of changes outside of the pseudoknot have also been shown to affect viral RNA replication in this system (16,26). The molecular basis for the effects on replication is largely unknown, but others have shown that viral RNA replication can be affected by both cis and trans mutations in positive-strand RNA viruses (17).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The A4, G3, C3, and GC3 mutations can be added to a collection of 3Ј nucleotide substitutions that disrupt replication. In general, AMV RNA replication is sensitive to nucleotide substitutions in the 3Ј UTR, and a number of changes outside of the pseudoknot have also been shown to affect viral RNA replication in this system (16,26). The molecular basis for the effects on replication is largely unknown, but others have shown that viral RNA replication can be affected by both cis and trans mutations in positive-strand RNA viruses (17).…”
Section: Discussionmentioning
confidence: 99%
“…To provide unequivocal evidence of RNA replication by detection of subgenomic RNA4, replication was activated in some experiments by a truncated RNA4 construct (AMV4-trUTR) wherein nucleotides 719 through 842 of the 3Ј untranslated region (Fig. 1B) were deleted (26).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations